1997
DOI: 10.1002/j.2161-1912.1997.tb00349.x
|View full text |Cite
|
Sign up to set email alerts
|

Multicultural Training for Undergraduates: Developing Knowledge and Awareness

Abstract: The changing demographics of the United States have lead to increased training of multicultural issues in graduate counseling programs. Graduate students report higher levels of multicultural competencies after completing a multicultural counseling course. Similarly, this study indicates increased multicultural awareness and knowledge among undergraduates completing a multicultural course.The changing demographics in the United States have pushed multicultural issues to the forefront of postsecondary education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…To meet this aim, the training intervention utilized perspective-taking to facilitate awareness of attitudes toward race-based mascots, conveyed specific knowledge about Native-themed mascots, and discussed social justice skills that can help interested participants become Although using classes as quasi-experimental groups does not constitute random assignment, this format allows for real-time assessment of multicultural curriculum. The use of classes of counseling students rather than randomly assigned groups has been evidenced in other studies (Robinson & Bradley, 1997;Seto, Young, Becker, & Kiselica, 2006) To address issues of power and influence in having the professor present the training intervention to students of a graded course, an outside researcher administered the pretest survey in the beginning of the semester while the professor was not in the room. Two weeks later, the 45-minute training interventions were given to the respective groups.…”
Section: Methodsmentioning
confidence: 99%
“…To meet this aim, the training intervention utilized perspective-taking to facilitate awareness of attitudes toward race-based mascots, conveyed specific knowledge about Native-themed mascots, and discussed social justice skills that can help interested participants become Although using classes as quasi-experimental groups does not constitute random assignment, this format allows for real-time assessment of multicultural curriculum. The use of classes of counseling students rather than randomly assigned groups has been evidenced in other studies (Robinson & Bradley, 1997;Seto, Young, Becker, & Kiselica, 2006) To address issues of power and influence in having the professor present the training intervention to students of a graded course, an outside researcher administered the pretest survey in the beginning of the semester while the professor was not in the room. Two weeks later, the 45-minute training interventions were given to the respective groups.…”
Section: Methodsmentioning
confidence: 99%
“…1 While a variety of scales have been used in evaluating the effects of diversity training (e.g., Multicultural Counseling Inventory (MCI), Attitudes Towards Inclusive Education scale (ATIES), we found that some studies used scales such as the Multicultural Awareness, Knowledge, and Skills Survey (MAKSS; D'Andrea, Daniels, & Heck, 1991) designed to examine awareness of one's attitudes toward ethnic minorities, knowledge concerning minority populations, and cross-cultural communication skills, and the Modern Racism scale (McConahay, 1981) used to assess explicit racial attitudes. For instance, the MAKSS scales were used in six studies in our review-most showing a positive change in cognitions, attitudes, and behaviors (Abernethy, 2005;D'Andrea et al, 1991;Diaz-Lazaro & Cohen, 2001;Guy-Walls, 2007;Murphy, Park, & Lonsdale, 2006;Robinson & Bradley, 1997). Further, it seems variables such as immediate response, awareness, behavior and attitude change have received the most attention in empirical research on diversity training (for exceptions see Dobbin et al, 2006;Ely, 2004a;Kellough & Naff, 2004;Naff & Kellough, 2003).…”
Section: Not Specified 106mentioning
confidence: 99%
“…Awareness training frequently emphasizes having people share experiences with one another (Roberson et al, 2001) and focuses on promoting participants' self-awareness on diversity-related issues such as cognitive biases and heuristics that may affect the interpretation of others' behavior (Probst, 2003). For instance, Robinson and Bradley (1997) point to an emphasis on an awareness of one's own cultural assumptions, values, and biases as well as knowledge of other worldviews. Some awareness training programs also cover other-awareness, for instance, Baba and Hebert (2004) described a training program that included modules on awareness of other cultures and ethnic backgrounds.…”
Section: Training Types: Awareness and Behavior-basedmentioning
confidence: 99%
“…Only three studies were located by this author that specifically examined the multicultural competencies of awareness and knowledge in undergraduate psychology programs, and each reported increases in awareness and knowledge after taking the course (Estrada, Durlak, & Juarex, 2002;Keim, Warring, & Rau 2001;Robinson & Bradley, 1997). However there was little discussion of the factors responsible for the change.…”
Section: Relevance Of the Present Studymentioning
confidence: 99%